Everyday experiences of racial discrimination among Chinese immigrants in Canada - Zhang, Weiguo; Tan, Weijia; Chen, Jinhua; Zhong, Zhuo Jun; Wang , Kunping; Zhao, Kedi (My University, 2024)
This study examined the everyday experiences of racism among Chinese immigrants in Canada. Data came from nine virtual focus groups comprising 48 participants of diverse genders and ages taking place in December 2021 and January 2022. We conducted our qualitative analysis by drawing on Essed's conceptualization of everyday racism and Crenshaw's conceptualization of intersectionality. Thematic and content analysis showed that racism against Chinese immigrants is more pervasive than previously recognized. Three-quarters of the participants disclosed instances of racism across various settings, including workplaces, schools, shops, airports, banks, hotels, restaurants, streets, and online. Some gender and age groups reported more incidents than others. Young men, on average, encountered the greatest number, followed by young and middle-aged women, while older men reported the fewest. Types of racist incidents also varied by age and gender. Young and middle-aged women encountered unsolicited intimate remarks and racism related to gender division of labour, while older adults, both men and women, faced racism associated with service provision. Younger men reported online racism. Some older participants remained unaware of the racist nature of their encounters, and middle-aged and older men tended to deny having experienced racist encounters. Given these findings, we suggest the need to raise awareness, establish empowerment initiatives, and adopt intersectionality approaches to address and combat racism against Chinese immigrants in Canada.
Keywords: racism; intersectionality; Chinese immigrant; Canada